Integrating clinical and genomic landscape analysis of perineural invasion identify ACTA1 as an oncogene for oral squamous cell carcinoma - Chen, Sheng; Zhao, Tongchao; Song, Yuxian; Huang, Xiaofeng; Ni, Yanhong; Ding, Liang; Fu, Yong; Hu, Qingang; Wang, Yi (Frontiers in Cell and Developmental Biology, 2024)
Background: Perineural invasion (PNI) has been shown to be a key pathological feature of several types of cancer, including oral squamous epithelial carcinoma (OSCC). However, the overall clinical and genomic landscape of PNI + OSCC are still unclear, and the molecular mechanism of PNI remains to be further investigated.Methods: 279 OSCC samples were extracted from the TCGA database and grouped according to PNI. The clinicopathological information, prognostic and survival analyses were performed. The Cibersort algorithm and ESTIMATE algorithm was used to estimate the impacts on proportion of immune cells, immune score and stromal score by PNI. Immunotherapy prediction analysis was also performed. 167 differentially expressed genes were screened for functional enrichment analysis. Actin α1 (ACTA1) protein, which was significantly up-regulated in the PNI + group, was selected for validation in our OSCC patient's cohort (n=70). We next analyzed the ratio and absolute number of key immunocytes in peripheral blood of OSCC patients according to Actin α1 expression by flow cytometry.Results: PNI was more likely to occur in patients with advanced tumors and worse prognosis. Immunomodulation analyses showed that T cells follicular helper and cells were significantly lower, but M2 macrophages and total stromal score was significantly higher in PNI + OSCC. Immunotherapy prediction analyses showed that PNI + OSCC may be more sensitive to CTLA4 inhibitor treatment. 167 differentially expressed genes were identified and enriched in muscle structure and cell movementrelated pathway. Among them, Actin α1 (ACTA1) was significantly up-regulated in PNI + advanced OSCC with worse clinical outcome whose had relatively low ratio of CD3 + CD8 + circulating cytotoxic T cells.PNI + OSCC patients with up-regulated of Actin α1 could benefit from cytotoxic T cellmediated immunotherapy.